Sintered body and its manufacturing method

JP7633545B2Active Publication Date: 2025-02-20NICHIA CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023118270
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-24
Filing Date
2023-07-20
Publication Date
2025-02-20
Estimated Expiration
2043-07-20

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、高い光の取り出し効率を維持しながら、光束を高めることができる、焼結体及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633545000007
    Figure 0007633545000007
  • Figure 0007633545000008
    Figure 0007633545000008
  • Figure 0007633545000009
    Figure 0007633545000009
Patent Text Reader

Abstract

To provide a sintered body high in a luminous flux, and a production method of the same.SOLUTION: A sintered body includes: a rear earth alminate fluorescent body crystal phase-including crystal-aggregated particle; and an aluminum oxide phase, where the aluminum oxide phase is disposed around the crystal-aggregated particle. A production method of a sintered body includes: preparing a first raw material mixture obtained by drying after subjecting to wet blending; subjecting the first raw material mixture and an aluminum oxide particle to dry blending; molding a mixture obtained by subjecting the first raw material mixture and the aluminum oxide particle to dry blending; and calcining a molded body obtained by molding the mixture.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a sintered body and a method for producing the same. [Background technology]

[0002] There is known a light emitting device that includes a light emitting diode (LED) or a laser diode (LD) and a wavelength conversion member containing a phosphor that converts the wavelength of light emitted from the LED or LD. Such a light emitting device is used as a light source for, for example, in-vehicle lighting, general lighting, backlights for liquid crystal display devices, projectors, etc.

[0003] As a wavelength conversion member provided in a light emitting device, for example, Patent Document 1 discloses a single-phase porous opto-ceramic having a density in a specific range with respect to the theoretical density. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-197774 A Summary of the Invention [Problem to be solved by the invention]

[0005] When the wavelength conversion member scatters light due to its porosity, if the density of the wavelength conversion member decreases due to its porosity, the luminous flux decreases, and the light extraction efficiency tends to decrease. Therefore, an object of the present disclosure is to provide a sintered body and a manufacturing method thereof that can increase luminous flux while maintaining high light extraction efficiency. [Means for solving the problem]

[0006] The first aspect is a sintered body including crystal agglomerates containing a rare earth aluminate phosphor crystal phase and an aluminum oxide phase, the aluminum oxide phase being disposed around the crystal agglomerates.

[0007] A second aspect is a method for producing a sintered body, the method including: preparing a first raw material mixture obtained by wet mixing and then drying; dry mixing the first raw material mixture with aluminum oxide particles; molding the mixture obtained by dry mixing the first raw material mixture with the aluminum oxide particles; and firing a molded body obtained by molding the mixture. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a sintered body and a manufacturing method thereof that can increase luminous flux while maintaining high light extraction efficiency. [Brief description of the drawings]

[0009] [Figure 1] 1 is a flowchart of a method for producing a sintered body. [Diagram 2] FIG. 1 is a diagram showing a schematic configuration of an example of a light emitting device. [Diagram 3] FIG. 1 is a plan view showing a schematic configuration of an example of a phosphor device including a sintered body. [Figure 4] FIG. 1 is a side view showing a schematic configuration of an example of a phosphor device including a sintered body. [Diagram 5] 2 is a SEM photograph of the sintered body according to Example 1. [Figure 6] 4 is a SEM photograph of a sintered body according to Example 2. [Figure 7] 4 is a SEM photograph of a sintered body according to Comparative Example 1. [Figure 8] 1 is a SEM photograph of a sintered body according to Comparative Example 2. [Figure 9] 1 is a SEM photograph of a sintered body according to Comparative Example 3. [Figure 10] 11 is a SEM photograph of a sintered body according to Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The sintered body and its manufacturing method according to the present invention will be described below based on the embodiments. However, the embodiments shown below are merely examples for embodying the technical idea of ​​the present invention, and the present invention is not limited to the sintered body and its manufacturing method described below. The relationship between the color name and the chromaticity coordinate, and the relationship between the wavelength range of light and the color name of monochromatic light are in accordance with JIS Z8110.

[0011] The sintered body includes crystal aggregate grains containing a rare earth aluminate phosphor crystal phase and an aluminum oxide phase, and the aluminum oxide phase is disposed around the crystal aggregate grains. In this specification, the rare earth aluminate phosphor crystal phase may be referred to as a "phosphor crystal phase". The rare earth aluminate phosphor may be referred to as a "phosphor". When the aluminum oxide phase is disposed around the crystal aggregate grains containing the phosphor crystal phase, the aluminum oxide phase, which has a higher thermal conductivity than the rare earth aluminate phosphor crystal phase, dissipates heat when absorbing excitation light incident on the sintered body and emitting light, thereby suppressing a decrease in luminous energy due to heat and increasing the luminous flux emitted from the sintered body. The thermal conductivity of a lutetium aluminum garnet phosphor having an yttrium aluminum garnet structure containing lutetium activated with Ce is about 8 Wm -1 ·K -1 and the thermal conductivity of aluminum oxide is 30Wm -1 ·K -1 It is.

[0012] It is preferable that the sintered body includes two or more crystal aggregate grains in a cross-sectional view, and an aluminum oxide phase is arranged between the two or more crystal aggregate grains. A cross-sectional view indicates, for example, viewing the surface or cross section of the sintered body in an SEM image measured using a scanning electron microscope (SEM). When an aluminum oxide phase is arranged between two or more crystal aggregate grains, heat generated when absorbing the energy of excitation light and emitting light is easily dissipated by the aluminum oxide phase, which has a higher thermal conductivity than the phosphor crystal phase, and a decrease in luminous energy due to heat can be suppressed, and light with a high luminous flux can be emitted.

[0013] When a sintered body is formed using the raw material of a rare earth aluminate phosphor, excess aluminum oxide contained in the composition of the rare earth aluminate phosphor may be liberated, forming an aluminum oxide phase. When excess aluminum enters the composition of the rare earth aluminate phosphor, it causes distortion in the crystal structure of the rare earth aluminate phosphor. When the crystal structure of the rare earth aluminate phosphor is distorted and the lattice points of the host crystal are shifted, the energy of the excitation light cannot be absorbed, and the energy for light emission may be lost due to thermal vibration of the distorted crystal structure, resulting in a decrease in luminous flux. For example, it is disclosed that the single-phase porous opto-ceramics disclosed in JP 2019-218560 A suppresses the formation of cracks in the ceramics by making the content of liberated Al2O3 less than 2.5% by volume.

[0014] In the sintered body, the aluminum oxide phase arranged around the crystal agglomerate grains is not composed of aluminum oxide resulting from excess aluminum liberated without being incorporated into the phosphor composition when aluminum oxide (hereinafter also referred to as "first aluminum oxide"), a raw material for forming the rare earth aluminate phosphor crystal phase, is used to form the rare earth aluminate phosphor crystal phase. By adding aluminum oxide (hereinafter also referred to as "second aluminum oxide") having a different size from the first aluminum oxide in addition to the first aluminum oxide, a raw material for forming the rare earth aluminate phosphor crystal phase, an aluminum oxide phase having a larger amount than the excess aluminum oxide liberated without being incorporated into the rare earth aluminate phosphor composition can be arranged around the crystal agglomerate grains. The aluminum oxide phase is not an aluminum oxide phase consisting only of aluminum oxide formed from first aluminum oxide, which is a raw material for forming the rare earth aluminate phosphor crystal phase, but is an aluminum oxide phase formed from second aluminum oxide of a different size from the first aluminum oxide.This makes it possible to efficiently release heat when the rare earth aluminate phosphor emits light and increase the luminous flux without distorting the host crystal structure of the rare earth aluminate phosphor.

[0015] The sintered body preferably contains an aluminum oxide phase having a maximum length of 1.0 μm or more on the surface or cross section of the sintered body. The first aluminum oxide (first aluminum oxide particles) as a raw material for forming the rare earth aluminate phosphor crystal phase preferably has a large BET specific surface area and a relatively small particle size in order to enhance reactivity with other raw materials. On the other hand, the second aluminum oxide (second aluminum oxide particles) forming the aluminum oxide phase arranged around the crystal aggregate grains containing the phosphor crystal phase preferably has a small BET specific surface area and a relatively large particle size in order to make it difficult to react with the raw material for forming the phosphor crystal phase. If the sintered body contains an aluminum oxide phase having a maximum length of 1.0 μm or more on the surface or cross section and the aluminum oxide phase is arranged around the crystal aggregate grains, it can be inferred that the aluminum oxide phase is not formed only from the excess first aluminum oxide not included in the composition of the phosphor crystal phase, but is formed from the second aluminum oxide having a size different from that of the first aluminum oxide. In this specification, the two most distant points on the contour of the aluminum oxide phase or crystal agglomerate grains on the surface or cross section of the sintered body to be measured are defined as the long diameter of the aluminum oxide phase or crystal agglomerate grains, and the maximum value of the long diameters of the aluminum oxide phase or crystal agglomerate grains on the surface or cross section of the sintered body to be measured is defined as the maximum length. The maximum length of the aluminum oxide phase on the surface or cross section of the sintered body may be 3.0 μm or less, 2.5 μm or less, or 2.0 μm or less.

[0016] The sintered body preferably contains an aluminum oxide phase in the range of 2.5 area% to 10.0 area% with respect to 100 area% of the surface or cross section of the sintered body. In the sintered body, if the aluminum oxide phase is arranged around the crystal aggregate grains and contains the aluminum oxide phase in the range of 2.5 area% to 10.0 area% with respect to 100 area% of the surface or cross section, the heat generated when the phosphor crystal phase absorbs the energy of the excitation light and emits light can be efficiently dissipated from the aluminum oxide phase, which has a higher thermal conductivity than the phosphor crystal phase, to increase the luminous flux. In the surface or cross section of the sintered body, the aluminum oxide phase may be contained in an amount of 3.0 area% or more, 4.0 area% or more, 4.5 area% or more, 9.5 area% or less, 9.0 area% or less, or 8.5 area% or less with respect to 100 area% of the surface or cross section. In a sintered body, the area ratio of the aluminum oxide phase to 100% of the surface or cross section of the sintered body can be determined from an SEM image measured using a scanning electron microscope (SEM).

[0017] The maximum length of the crystal aggregate grains on the surface or cross section of the sintered body is preferably in the range of 10.0 μm to 150.0 μm. The maximum length of the crystal aggregate grains on the surface or cross section of the sintered body is more preferably in the range of 60.0 μm to 130.0 μm, and even more preferably in the range of 70.0 μm to 120.0 μm. If the maximum length of the crystal aggregate grains on the surface or cross section of the sintered body is in the range of 10.0 μm to 150.0 μm, the excitation light incident on the sintered body is easily absorbed and wavelength converted by the phosphor crystal phase contained in the crystal aggregate grains, and the decrease in the luminous flux emitted from the sintered body is suppressed, and light with a high luminous flux can be emitted from the sintered body. If the maximum length of the crystal aggregate grains on the surface or cross section of the sintered body is in the range of 10.0 μm to 150.0 μm, the crystal aggregate grains are larger than the aluminum oxide phase, and the aluminum oxide phase is easily arranged around the crystal aggregate grains. Furthermore, when the crystal aggregate grains are larger than the rare earth aluminate crystal phase, the aluminum oxide phase is likely to be disposed between two or more crystal aggregate grains.

[0018] The area of ​​the measurement range on the surface or cross section of the sintered body is 48387 μm in the SEM image measured using a SEM. 2 In the measurement range on the surface or cross section of the sintered body, the major axis and maximum length of the aluminum oxide phase, the area ratio of the aluminum oxide phase to 100% of the area of ​​the measurement range, and the major axis and maximum length of the crystal aggregate grains can be measured. 2 In the region, the major axis, maximum length and area ratio of the aluminum oxide phase, as well as the major axis and maximum length of the crystal aggregate grains can be accurately measured.

[0019] In the sintered body, the aluminum oxide phase is preferably in the range of 2.5 volume % or more and 10.0 volume % or less relative to the total 100 volume % of the crystal aggregate grains and the aluminum oxide phase. The aluminum oxide phase may be in the range of 3.0 volume % or more and 9.5 volume % or less, 4.0 volume % or more and 9.0 volume % or less, or 4.5 volume % or more and 8.5 volume % or less relative to the total 100 volume % of the crystal aggregate grains and the aluminum oxide phase. When the aluminum oxide phase is in the range of 2.5 volume % or more and 10.0 volume % or less in the sintered body, the aluminum oxide phase is easily arranged around the crystal aggregate grains, and the aluminum oxide phase is easily arranged between two or more crystal aggregate grains. In the sintered body, the volume ratio of the aluminum oxide phase to the total 100 volume % of the crystal aggregate grains and the aluminum oxide phase can be obtained from an SEM image measured using an SEM, similar to the area ratio of the aluminum oxide phase to 100 area % of the surface or cross section of the sintered body. This is because it can be assumed that the aluminum oxide phase in the sintered body, which is present on the surface or cross section of the sintered body, also exists in the thickness direction.

[0020] The rare earth aluminate phosphor crystal phase preferably contains at least one element selected from the group consisting of Y, La, Lu, Gd, and Tb. When the rare earth aluminate phosphor crystal phase contains at least one element selected from the group consisting of Y, La, Lu, Gd, and Tb, it becomes easier to obtain a rare earth aluminate phosphor crystal phase having a composition that absorbs incident excitation light and converts the wavelength of the light into a desired color tone.

[0021] The rare earth aluminate phosphor crystal phase preferably has a composition contained in the composition formula represented by the following formula (I): When the rare earth aluminate phosphor crystal phase has the composition represented by the following formula (I), it is possible to absorb excitation light and emit light whose wavelength has been converted to a desired color tone. (R 1 1-n Ce n )3(Al 1-m M 1 m ) 5k O 12 (I) (In the above formula (I), R 1 is at least one element selected from the group consisting of Y, La, Lu, Gd and Tb, and M 1 is at least one element selected from the group consisting of Ga and Sc, and m, n, and k satisfy 0≦m≦0.02, 0.001≦n≦0.017, and 0.95≦k≦1.10, respectively.

[0022] In the composition represented by the above formula (I), R 1 may contain two or more rare earth elements. Ce is an activator element for the rare earth aluminate phosphor crystal phase, and the product of the variables n and 3 represents the molar ratio of Ce in the composition represented by formula (I). The variable n is more preferably 0.002 or more and 0.016 or less (0.002≦n≦0.016), and further preferably 0.003 or more and 0.015 or less (0.003≦n≦0.015). In the composition represented by formula (I), the product of the variables m, 5, and k represents the molar ratio of element M 1 The molar ratio of element M 1may not be included in the composition represented by formula (I), that is, m may be 0. In the composition represented by formula (I), in order to convert the wavelength to a desired color tone, the variable m may be 0.00001 or more and 0.02 or less (0.00001≦m≦0.02), or 0.00005 or more and 0.018 or less (0.00005≦m≦0.018). In the composition represented by formula (I), the product of the variable k and 5 is the sum of Al and the element M. 1 The variable k is more preferably 0.96 or more and 1.09 or less (0.96≦k≦1.09), and further preferably 0.97 or more and 1.08 or less (0.97≦k≦1.08).

[0023] The relative density of the sintered body is preferably 90% or more, more preferably 93% or more, and preferably 95% or more, and may be 100% or less than 99%. When the relative density of the sintered body is within the range of 90% to 100%, heat generated when the excitation light incident on the sintered body is wavelength-converted in the phosphor crystal phase is efficiently dissipated from the aluminum oxide phase arranged around the phosphor crystal phase, so that the sintered body can emit wavelength-converted light with a high luminous flux.

[0024] The relative density of the sintered body can be calculated from the apparent density and true density of the sintered body by the following formula (1).

[0025]

number

[0026] The apparent density of a sintered body is the mass of the sintered body divided by the volume of the sintered body, and can be calculated by the following formula (2). The true density of the sintered body can be calculated by using the true density of the phosphor and the true density of aluminum oxide (aluminum oxide particles) according to the following formula (3). The porosity of the sintered body is the remainder obtained by subtracting the relative density of the sintered body from 100%.

[0027]

number

[0028]

number

[0029] The sintered body can be used as a reflective wavelength conversion member in which the incident surface (first main surface) into which the excitation light is incident and the exit surface (first main surface) from which the wavelength-changed light is emitted are the same surface. When the sintered body is used as a reflective wavelength conversion member, there is no limitation on the thickness of the sintered body, and when the sintered body is a plate-shaped body, the plate thickness is preferably within the range of 90 μm to 250 μm, more preferably within the range of 100 μm to 240 μm, in order to improve the light extraction efficiency.

[0030] When the sintered body has a plate-like shape and the incident surface into which the excitation light is incident and the exit surface from which the light is emitted are the same surface, the diameter of the exiting light is preferably less than 102%, more preferably 101% or less, when the diameter of the incident light is 100%. In this way, if the diameter of the exiting light emitted from the same surface as the incident surface is less than 102% of the diameter of the incident light, the spread of the exiting light is suppressed and is maintained, and the light emitted from the sintered body can be easily focused at a target position. The diameter of the incident light incident on one surface of the sintered body is the diameter of the light emitted from the light source. The diameter of the incident light can be measured, for example, by a color luminance meter. The diameter of the incident light is preferably in the range of 0.1 mm to 5 mm, more preferably in the range of 0.5 mm to 4 mm. The diameter of the outgoing light emitted from the same surface of the sintered body as the surface into which the incident light was incident can be measured by measuring the luminance of the light emitted from the sintered body using a color luminance meter, setting the position showing the maximum luminance in the obtained emission spectrum as the center (measurement center), measuring the absolute distance (mm) from the measurement center to two positions where the luminance is 10 / 100 of the maximum luminance in the emission spectrum (hereinafter sometimes referred to as "10 / 100 luminance"), and measuring the sum of the absolute values ​​of the distances (mm) from the measurement center to two positions where the luminance is from the maximum luminance to 10 / 100 of the maximum luminance in the emission spectrum.

[0031] The method for producing a sintered body includes preparing a first raw material mixture obtained by wet mixing and then drying, dry mixing the first raw material mixture with aluminum oxide particles, molding the mixture obtained by dry mixing the first raw material mixture with the aluminum oxide particles, and firing the molded body obtained by molding the mixture.

[0032] Fig. 1 is a flow chart showing an example of a method for producing a sintered body. The method for producing a sintered body will be described with reference to Fig. 1. The method for producing a sintered body includes steps of preparing a first raw material mixture (S101), dry-mixing the first raw material mixture with aluminum oxide particles (S102), molding the mixture (S103), and firing the molded body (S104).

[0033] When preparing the first raw material mixture, the first raw material mixture contains at least one rare earth element R selected from the group consisting of Y, La, Lu, Gd, and Tb. 1 a first oxide particle containing Ce, a second oxide particle containing Al, and a third oxide particle containing at least one element M selected from Ga and Sc as necessary. 1 and optionally rare earth aluminate phosphor particles.

[0034] Specifically, the first oxide particles include yttrium oxide particles, lanthanum oxide particles, lutetium oxide particles, gadolinium oxide particles, and terbium oxide particles. The second oxide particles include cerium oxide particles. The third oxide particles include aluminum oxide particles. The fourth oxide particles include gallium oxide particles and scandium oxide particles.

[0035] When the third oxide particles containing Al are aluminum oxide particles, the aluminum oxide particles that are the third oxide particles containing Al contained in the first raw material mixture are also referred to as "first aluminum oxide particles". The third oxide particles (first aluminum oxide particles) preferably have a larger BET specific surface area and a smaller particle size than the aluminum oxide particles (hereinafter also referred to as "second aluminum oxide particles") that are dry-mixed with the first raw material mixture described below. When the first aluminum oxide particles that are the third oxide particles contained in the first raw material mixture have a larger BET specific surface area than the second aluminum oxide particles and a smaller particle size than the second aluminum oxide particles, they are highly reactive with each oxide particle contained in the first raw material mixture, and are preferably likely to form a rare earth aluminate phosphor crystal phase having a composition represented by the above formula (I), and the distortion of the crystal structure of the rare earth aluminate phosphor crystal phase is suppressed, and the lattice points of the host crystal are not shifted, so that the energy of the excitation light can be efficiently absorbed and wavelength-converted light with a high luminous flux can be emitted from the phosphor crystal phase. The third oxide particles containing Al, for example the first aluminum oxide particles, have a BET specific surface area of ​​10.0 m 2 / g over 15.0m2 The BET specific surface area of ​​the third oxide particles containing Al is preferably within the range of 10.0 m 2 / g over 15.0m 2 If the specific surface area of ​​the third oxide particles containing Al is within the range of 10.5 m / g or less, the reactivity with the oxide particles contained in the first raw material mixture is high, and a rare earth aluminate phosphor crystal phase having a desired composition can be formed. 2 / g or more 14.5m 2 / g or less, and 2 / g or more 14.0m 2 / g or less, and 2 / g or more 13.5m 2 / g or less.

[0036] The oxide particles contained in the first raw material mixture are preferably mixed in a molar ratio that results in the composition represented by formula (I) above.

[0037] When the oxides contained in the first raw material mixture are blended, for example, in a molar ratio that results in the composition represented by formula (I), it is preferable that the rare earth aluminate phosphor particles contained in the first raw material mixture have the composition represented by formula (I).

[0038] When the first raw material mixture contains rare earth aluminate phosphor particles, the mass ratio of the rare earth aluminate phosphor particles is preferably in the range of 10 mass% to 90 mass%, more preferably in the range of 12 mass% to 80 mass%, and more preferably in the range of 15 mass% to 70 mass% relative to the total of 100 mass% of the first oxide particles, the second oxide particles, the third oxide particles, and, if necessary, the fourth oxide particles. When the first raw material mixture contains rare earth aluminate phosphor particles within the above mass ratio range, it may be easy to obtain a sintered body containing crystal aggregate particles of a desired size such that the aluminum oxide phase is arranged around the crystal aggregate particles containing the rare earth aluminate phosphor crystal phase. The rare earth aluminate phosphor particles contained in the first raw material mixture may be rare earth aluminate phosphor particles formed by a coprecipitation method. The rare earth aluminate phosphor particles formed by a coprecipitation method have a large specific surface area and are easy to form crystal aggregate particles containing the rare earth aluminate phosphor crystal phase.

[0039] The first raw material mixture is preferably wet-mixed. By wet-mixing the first raw material mixture, the first to fourth oxide particles, and, if necessary, rare earth aluminate phosphor particles, are uniformly dispersed in the liquid, and crystal aggregate particles containing a homogeneous rare earth aluminate phosphor crystal phase are formed. Examples of the liquid used when wet-mixing the first raw material mixture include deionized water, water, and ethanol. The liquid used when wet-mixing the first raw material mixture is preferably in the range of 10 parts by mass to 200 parts by mass, and may be in the range of 40 parts by mass to 150 parts by mass, relative to 100 parts by mass of the first raw material mixture.

[0040] The first raw material mixture to be wet-mixed may contain a dispersant. For example, an organic dispersant may be used as the dispersant, and a cationic dispersant, an anionic dispersant, a nonionic dispersant, or the like may be used. When a dispersant is added to the first raw material mixture, the amount of the dispersant is preferably such that the dispersant volatilizes upon thermal degreasing or baking, and is preferably 10% by mass or less, or may be 5% by mass or less, or may be 3% by mass or less, relative to 100% by mass of the first raw material mixture.

[0041] The first raw material mixture is wet-mixed and then dried to obtain a first raw material mixture. The drying temperature may be in the range of 50°C to 150°C, and the drying time may be 1 hour to 20 hours. By wet-mixing and drying the first raw material mixture, a first raw material mixture in which the first to fourth oxides and the raw materials of the rare earth aluminate phosphor particles, which are included as necessary, are uniformly mixed can be obtained.

[0042] The BET specific surface area of ​​the aluminum oxide particles (second aluminum oxide particles) to be dry-mixed with the first raw material mixture is preferably smaller than the BET specific surface area of ​​the Al-containing third oxide particles contained in the first raw material mixture. Since the second aluminum oxide particles have a smaller BET specific surface area than the Al-containing third oxide particles, they are less likely to react with each oxide particle in the first raw material mixture, and an aluminum oxide phase formed from the second aluminum oxide particles is more likely to be formed around the crystal aggregate grains formed from the first raw material mixture.

[0043] The aluminum oxide particles (second aluminum oxide particles) to be dry mixed with the first raw material mixture have a BET specific surface area of ​​1.0 m 2 / g or more 10.0m 2 The BET specific surface area of ​​the aluminum oxide particles (second aluminum oxide particles) to be dry-mixed with the first raw material mixture is preferably within the range of 1.0 m 2 / g or more 10.0m 2 If the BET specific surface area of ​​the second aluminum oxide particles is within the range of 1.5 m / g or less, the second aluminum oxide particles are unlikely to react with each oxide particle in the first raw material mixture due to their small BET specific surface area, and an aluminum oxide phase formed from second aluminum oxide particles having a size that can easily dissipate heat generated by the phosphor crystal phase is likely to be formed around the crystal agglomerates formed from the first raw material mixture. The BET specific surface area of ​​the aluminum oxide particles (second aluminum oxide particles) to be dry-mixed with the first raw material mixture is 1.5 m 2 / g or more 9.0m 2 / g or less, and 2.0m 2 / g or more 8.0m 2 / g or less, and 2 / g or more 7.0m 2 / g or less.

[0044] The method for producing a sintered body includes dry-mixing a first raw material mixture obtained by drying after wet mixing with aluminum oxide particles (second aluminum oxide particles). The dry mixing is preferably performed, for example, in a ball mill for 10 minutes or more and 2 hours or less. After the dry mixing, the mixture may be passed through a sieve with an opening of 350 μm or less. When the first raw material mixture and the aluminum oxide particles are dry-mixed, they are not mixed as evenly as when wet-mixed. By firing the dry-mixed first raw material mixture and the aluminum oxide particles that are not mixed as evenly as when wet-mixed, crystal aggregate particles containing a rare earth aluminate phosphor crystal phase are formed from the first raw material mixture, and a sintered body in which an aluminum oxide phase is arranged around the crystal aggregate particles is easily obtained. The mixture containing the first raw material mixture and the aluminum oxide particles may be dry-powder mixed, with a portion of the mixture being pulverized.

[0045] The aluminum oxide particles (second aluminum oxide particles) are preferably contained in a range of 2.5 volume % to 10.0 volume % relative to the total amount 100 volume % of the first raw mixture and the aluminum oxide particles. By using a mixture obtained by dry mixing the first raw mixture and the aluminum oxide particles so that the aluminum oxide particles are contained in a range of 2.5 volume % to 10.0 volume % relative to the total amount 100 volume % of the first raw mixture and the aluminum oxide particles, a sintered body in which the aluminum oxide phase is contained in a range of 2.5 volume % to 10.0 volume % relative to the total amount 100 volume % of the crystal aggregate grains and the aluminum oxide phase can be obtained. The aluminum oxide particles may be contained in a range of 3.0 volume % or more, 4.0 volume % or more, 4.5 volume % or more, 9.5 volume % or less, 9.0 volume % or less, or 8.5 volume % or less relative to the total amount 100 volume % of the first raw mixture and the aluminum oxide particles.

[0046] The method for producing a sintered body includes molding the mixture obtained by dry mixing. The method for molding the mixture obtained by dry mixing can employ known methods such as press molding. Examples of press molding methods include die press molding and cold isostatic pressing (CIP) method, the term of which is defined in JIS Z2500:2000, No. 2109. Alternatively, molding may be performed by uniaxial compression. As a molding method, two types of methods may be adopted to adjust the shape of the molded body, for example, CIP may be performed after die press molding, or CIP may be performed after uniaxial compression by the roller bench method. As for CIP, it is preferable to press the molded body by cold isostatic pressing using water as a medium.

[0047] The pressure during die press molding or uniaxial compression molding is preferably in the range of 5 MPa to 50 MPa, more preferably 5 MPa to 30 MPa. If the pressure during die press molding or uniaxial compression molding is in the above range, the molded body can be shaped into a desired shape.

[0048] The pressure in the CIP is preferably in the range of 50 MPa to 200 MPa, more preferably in the range of 50 MPa to 180 MPa. When the pressure in the CIP is in the range of 50 MPa to 200 MPa, a sintered body can be obtained that includes crystal agglomerates containing a rare earth aluminate phosphor crystal phase and an aluminum oxide phase arranged around the crystal agglomerates.

[0049] The molded body obtained by molding the mixture may be heated to remove the dispersant and the like and degrease the molded body. When the molded body is heated to degrease the molded body, it is preferable to heat the molded body in the air or nitrogen atmosphere at a temperature in the range of 500° C. to 1000° C. By heating the molded body in the air or nitrogen atmosphere at a temperature in the range of 500° C. to 1000° C., the amount of carbon contained in the molded body is reduced, and the decrease in luminous flux due to the inclusion of carbon can be suppressed.

[0050] The method for producing a sintered body includes firing the molded body obtained by molding. When firing the molded body, the firing temperature (temperature in the firing furnace) is preferably in the range of 1300°C to 1800°C, more preferably in the range of 1400°C to 1790°C, even more preferably in the range of 1450°C to 1780°C, may be in the range of 1500°C to 1700°C, or may be in the range of 1550°C to 1650°C. When firing the molded body, if the firing temperature is 1300°C or higher, a sintered body containing crystal aggregate grains containing a rare earth aluminate phosphor crystal phase and an aluminum oxide phase arranged around the crystal aggregate grains can be obtained. When firing the molded body, if the firing temperature is 1800°C or lower, a sintered body containing voids dispersed around each crystal phase in the cross section of the sintered body and in which the grain boundaries of each crystal phase can be distinguished can be obtained without dissolving the molded body so that the grain boundaries of each crystal phase disappear.

[0051] The molded body is preferably fired in an oxygen-containing atmosphere. The oxygen content in the atmosphere is preferably 5% by volume or more, more preferably 10% by volume or more, and even more preferably 15% by volume or more. The molded body may be fired in an air atmosphere (oxygen content of 20% by volume or more). In an atmosphere with an oxygen content of less than 1% by volume, the surface of the oxide is difficult to melt, crystal aggregate particles containing a rare earth aluminate phosphor crystal phase are difficult to form, and an aluminum oxide phase may be difficult to arrange around the crystal aggregate particles. The amount of oxygen in the atmosphere may be measured, for example, by the amount of oxygen flowing into a firing device, and may be measured at a temperature of 20°C and atmospheric pressure (101.325 kPa). The pressure when firing the molded body may be atmospheric pressure (101.325 kPa).

[0052] The obtained sintered body may be annealed in a reducing atmosphere. By annealing the obtained sintered body in a reducing atmosphere, cerium, which is an oxidized activation element contained in the rare earth aluminate phosphor crystal phase in the sintered body, is reduced, and the decrease in wavelength conversion efficiency and the decrease in luminous efficiency in each crystal phase can be suppressed. The reducing atmosphere may be an atmosphere containing at least one rare gas selected from the group consisting of helium, neon, and argon, or nitrogen gas, and hydrogen gas or carbon monoxide gas, and more preferably contains at least argon or nitrogen gas, and hydrogen gas or carbon monoxide gas. The annealing treatment may be performed after processing.

[0053] The annealing temperature is lower than the firing temperature and is preferably within the range of 1000° C. to 1600° C. The annealing temperature is more preferably within the range of 1100° C. to 1400° C. If the annealing temperature is lower than the firing temperature and within the range of 1000° C. to 1600° C., it is possible to reduce cerium, which is an oxidized activator element contained in the rare earth aluminate phosphor crystal phase in the sintered body, without reducing the voids in the sintered body, and to suppress a decrease in the efficiency of wavelength conversion and a decrease in luminous flux.

[0054] The obtained sintered body may be cut into a desired size or thickness by any known method, such as blade dicing, laser dicing, or a method using a wire saw.

[0055] The obtained sintered body may be surface-treated. In the surface treatment, the surface of the cut piece obtained by cutting the obtained sintered body is surface-treated. This surface treatment not only makes it possible to make the surface of the sintered body in an appropriate state in order to increase the light extraction efficiency of the sintered body, but also makes it possible to make the sintered body into a desired shape, size, or thickness by cutting the sintered body into a desired size or thickness or by surface treatment alone. The surface treatment may be performed before or after cutting the sintered body into a desired size or thickness and processing it. Examples of methods for surface treatment include a method using sandblasting, a method using mechanical grinding, a method using dicing, and a method using chemical etching.

[0056] The above-mentioned manufacturing method can provide a sintered body that includes crystal aggregate grains containing a rare earth aluminate phosphor crystal phase and an aluminum oxide phase, with the aluminum oxide phase being disposed around the crystal aggregate grains. The rare earth aluminate phosphor crystal phase contained in the sintered body obtained by the above-mentioned manufacturing method preferably has a composition represented by formula (I).

[0057] The obtained sintered body can be used as a wavelength conversion member in a light emitting device such as a light source for a projector by combining it with a light source.

[0058] A light emitting device using the above-mentioned sintered body as a wavelength conversion member will be described. The light emitting device includes the sintered body and an excitation light source.

[0059] The excitation light source is preferably a semiconductor light-emitting element made of an LED chip or an LD chip. The semiconductor light-emitting element can be a nitride-based semiconductor. By using a semiconductor light-emitting element as the excitation light source, a highly efficient light-emitting device with high output linearity relative to the input and high mechanical shock resistance can be obtained. The sintered body can convert the wavelength of light emitted from the semiconductor light-emitting element to form a light-emitting device that emits wavelength-converted mixed color light. The semiconductor light-emitting element is preferably one that emits light in a wavelength range of, for example, 350 nm or more and 500 nm or less. The sintered body is preferably one that converts the wavelength of the excitation light from the semiconductor light-emitting element to emit an emission light having an emission peak wavelength of 500 nm or more and less than 650 nm.

[0060] The light emitting element is more preferably a laser diode. The excitation light emitted from the laser diode as the excitation light source is made incident on the wavelength conversion member, and the light whose wavelength is converted by the phosphor contained in the ceramic composite of the wavelength conversion member is condensed, and separated into red light, green light, and blue light by a plurality of optical systems such as a lens array, a polarization conversion element, and a color separation optical system, and modulated according to image information to form color image light. The excitation light emitted from the laser diode as the excitation light source may be made incident on the wavelength conversion member through an optical system such as a dichroic mirror or a collimating optical system.

[0061] FIG. 2 is a schematic diagram showing an example of a configuration of a light emitting device 100. The arrows in FIG. 2 are schematic diagrams showing the optical paths of light. The light emitting device 100 preferably includes an excitation light source 101, which is a light emitting element, a collimating lens 102, three condenser lenses 103, 105, and 106, a dichroic mirror 104, a rod integrator 107, and a wavelength conversion device 120 including a wavelength conversion member. The excitation light source 101 preferably uses a laser diode. The excitation light source 101 may use a plurality of laser diodes, or may be one in which a plurality of laser diodes are arranged in an array or matrix. The collimating lens 102 may be a collimating lens array in which a plurality of collimating lenses are arranged in an array. The laser light emitted from the excitation light source 101 becomes approximately parallel light by the collimating lens 102, is collected by the condenser lens 103, passes through the dichroic mirror 104, and is further collected by the condenser lens 105. The laser light collected by the condenser lens 105 is wavelength-converted by the wavelength conversion device 120 including the wavelength conversion member 110 and the light reflector 122, and light having an emission peak wavelength in a desired wavelength range is emitted from the wavelength conversion member 110 side of the wavelength conversion device 120. The wavelength-converted light emitted from the wavelength conversion device 120 is collected by the condenser lens 106 and incident on the rod integrator 107, and light with improved uniformity of illuminance distribution in the illuminated area is emitted from the light emitting device 100.

[0062] Fig. 3 is a schematic diagram showing a planar configuration of an example of the wavelength conversion device 120. In Fig. 4, the wavelength conversion device 120 is shown in a side view as one of the members constituting the light emitting device 100. The wavelength conversion device 120 includes at least a wavelength conversion member 110. The wavelength conversion device 120 includes a disk-shaped wavelength conversion member 110, and may include a rotation mechanism 121 for rotating the wavelength conversion member 110. The rotation mechanism 121 is connected to a drive mechanism such as a motor, and can dissipate heat by rotating the wavelength conversion member 110.

[0063] FIG. 4 is a schematic diagram showing the configuration of a side of an example of the wavelength conversion device 120, which is shown in a side view in FIG. 2 as one of the members constituting the light emitting device 100. The wavelength conversion device 120 includes a sintered body 111 and a light-transmitting thin film 112 as the wavelength conversion member 110. The wavelength conversion device 120 includes a light reflector 122 on the side opposite to the side on which the light-transmitting thin film 112 of the sintered body 111 of the wavelength conversion member 110 is disposed. If the light from the sintered body 111 can be sufficiently emitted to the side on which the light-transmitting thin film 112 is disposed, the light reflector 122 can be omitted. The light reflector 122 may be used not only as a member that reflects the light from the sintered body 111 to the side on which the light-transmitting thin film 112 is disposed, but also as a heat dissipation member that transfers heat generated in the sintered body 111 and dissipates it to the outside.

[0064] Embodiments according to the present invention include the following sintered body and a method for producing the same.

[0065] [Section 1] The phosphor has a rare earth aluminate phosphor crystal phase and an aluminum oxide phase. The sintered body, wherein the aluminum oxide phase is disposed around the crystal aggregate grains. [Section 2] Item 2. The sintered body according to item 1, wherein, in one cross-sectional view, the sintered body includes two or more of the crystal agglomerate grains, and the aluminum oxide phase is disposed between the two or more crystal agglomerate grains. [Section 3] Item 3. The sintered body according to item 1 or 2, wherein the surface or cross section of the sintered body contains the aluminum oxide phase having a maximum length of 1.0 μm or more. [Section 4] Item 4. The sintered body according to any one of items 1 to 3, wherein the aluminum oxide phase is contained in a surface or cross section of the sintered body in a range of 2.5 area% to 10.0 area% relative to 100 area% of the surface or cross section. [Section 5] The area of ​​the measurement range on the surface or cross section of the sintered body is 48387 μm in an SEM image measured using a scanning electron microscope. 2 Item 5. The sintered body according to item 4, wherein the sintered body is in the range of 0.1 to 1.0 mm. [Section 6] Item 6. The sintered body according to any one of items 1 to 5, wherein the maximum length of the crystal aggregate grains on the surface or cross section of the sintered body is in the range of 10.0 μm to 150.0 μm. [Section 7] The area of ​​the measurement range on the surface or cross section of the sintered body is 48387 μm in an SEM image measured using a scanning electron microscope. 2 Item 7. The sintered body according to item 6, wherein the sintered body is in the range of 0.1 to 1. [Section 8] 8. The sintered body according to any one of items 1 to 7, wherein the aluminum oxide phase is in the range of 2.5 vol% to 10.0 vol% relative to 100 vol% of the total of the crystal agglomerates and the aluminum oxide phase. [Section 9] Item 9. The sintered body according to any one of items 1 to 8, wherein the rare earth aluminate phosphor crystal phase contains at least one element selected from the group consisting of Y, La, Lu, Gd, and Tb. [Section 10] Item 10. The sintered body according to any one of items 1 to 9, wherein the rare earth aluminate phosphor crystal phase has a composition represented by the following formula (I): (R 1 1-n Ce n )3(Al 1-m M 1 m ) 5k O 12 (I) (In the above formula (I), R 1 is at least one element selected from the group consisting of Y, La, Lu, Gd and Tb, and M 1 is at least one element selected from the group consisting of Ga and Sc, and m, n, and k satisfy 0≦m≦0.02, 0.001≦n≦0.017, and 0.95≦k≦1.10, respectively. [Section 11] preparing a first raw material mixture obtained by wet mixing and then drying; dry mixing the first raw material mixture with aluminum oxide particles; shaping a mixture obtained by dry-mixing the first raw material mixture and the aluminum oxide particles; and sintering the resulting molded body by molding the mixture. [Section 12] When preparing the first raw material mixture, the first raw material mixture contains at least one element R selected from the group consisting of Y, La, Lu, Gd, and Tb. 1 a first oxide particle containing Ce; a second oxide particle containing Al; and, if necessary, at least one element M selected from the group consisting of Ga and Sc. 1 Item 12. A method for producing a sintered body according to item 11, further comprising the step of: [Section 13] The BET specific surface area of ​​the aluminum oxide particles to be dry-mixed with the first raw material mixture is 1.0 m 2 / g or more 10.0m 2 Item 13. The method for producing a sintered body according to item 11 or 12, wherein the sintered body has a molecular weight of 1000 or less. [Section 14] Item 14. The method for producing a sintered body according to any one of items 11 to 13, wherein the BET specific surface area of ​​the aluminum oxide particles is smaller than the BET specific surface area of ​​the third oxide particles containing Al. [Section 15] The BET specific surface area of ​​the third oxide particles containing Al is 10.0 m 2 / g over 15.0m 2 Item 15. The method for producing a sintered body according to any one of items 12 to 14, wherein the sintered body has a molecular weight of 1000 or less. [Section 16] Item 16. The method for producing a sintered body according to any one of items 11 to 15, wherein the aluminum oxide particles are contained in a range of 2.5 vol% to 10.0 vol% relative to 100 vol% of a total amount of the first raw material mixture and the aluminum oxide particles. [Section 17] Item 17. The method for producing a sintered body according to any one of items 11 to 16, wherein the sintering temperature is in the range of 1300° C. or more and 1800° C. or less when the molded body is sintered. EXAMPLES

[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0067] The first oxide particles are made of lutetium oxide having a purity of 99% by mass and a BET specific surface area of ​​12.2 m 2 / g of lutetium oxide particles were used.

[0068] The second oxide particles are cerium oxide having a purity of 92% by mass and a BET specific surface area of ​​124.9 m 2 / g of cerium oxide particles were used.

[0069] The third oxide particles are aluminum oxide particles having a purity of 99% by mass and a BET specific surface area of ​​12.2 m 2 Aluminum oxide particles (first aluminum oxide particles) having a particle size of 0.1 μm / g were used.

[0070] Example 1 The molar ratio of each element of Lu, Al, and Ce contained in each oxide particle is Lu 2.987 Ce 0.013 AlO 12 Lutetium oxide particles as the first oxide particles, cerium oxide particles as the second oxide particles, and aluminum oxide particles (first aluminum oxide particles) as the third oxide particles were weighed out so as to obtain a composition represented by the following formula: Relative to a total amount of 100 parts by mass of the first oxide particles, second oxide particles, and third oxide particles, 4.0 parts by mass of a dispersant (Floren G-700, Kyoeisha Chemical Co., Ltd.) was added, and 50 parts by mass of ethanol was further added. The mixture was wet-mixed using a ball mill, dried at 130°C for 10 hours, and then dry-pulverized and mixed using a ball mill to prepare a first raw material mixture.

[0071] The aluminum oxide particles (second aluminum oxide particles) to be dry mixed with the first raw material mixture have an aluminum oxide purity of 99% by mass or more and a BET specific surface area of ​​5.3 m 2 / g secondary aluminum oxide particles were used.

[0072] The second aluminum oxide particles were added so that the amount (volume %) of the second aluminum oxide particles was shown in Table 1, relative to 100 volume % of the total amount of the first raw material mixture and the aluminum oxide particles (second aluminum oxide particles). The first raw material mixture and the second aluminum oxide particles were dry mixed for 15 minutes using a ball mill.

[0073] The mixture obtained was filled into a mold and subjected to a pressure of 5 MPa (51 kgf / cm 2 A cylindrical molded body with a diameter of 26 mm and a thickness of 8 mm was formed at a pressure of 100 MPa. The obtained molded body was placed in a packaging container, vacuum-packed, and subjected to CIP at 176 MPa using a cold isostatic pressurizing device (manufactured by Kobe Steel, Ltd. (KOBELCO)) to obtain a molded body. The obtained molded body was heated and degreased at 700°C in a nitrogen atmosphere.

[0074] The compact obtained by molding was sintered in a sintering furnace (manufactured by Marusho Denki Co., Ltd.) to obtain a sintered body. The sintering conditions were an air atmosphere (101.325 kPa, oxygen concentration: approximately 20% by volume), a temperature of 1560°C, and a sintering time of 6 hours. The obtained sintered body was cut into an appropriate shape and size with a wire saw, and the surface of the cut pieces was polished with a surface grinder. Finally, a sintered body according to Example 1 having a plate thickness of 230 μm was obtained. The sintered body according to Example 1 was obtained by sintering Lu 2.987 Ce 0.013 AlO 12 The sintered body contained crystal aggregate grains containing a rare earth aluminate phosphor crystal phase having a composition represented by the formula: and an aluminum oxide phase having a maximum length of 1.0 μm or more on the surface or cross section of the sintered body. The aluminum oxide phase was arranged around the crystal aggregate grains.

[0075] Example 2 A sintered body according to Example 2 was obtained in the same manner as in Example 1, except that the amount of the second aluminum oxide particles was the amount (volume %) shown in Table 1, relative to the total volume 100% of the first raw material mixture and the aluminum oxide particles (second aluminum oxide particles). 2.987 Ce 0.013 AlO12 and an aluminum oxide phase having a maximum length of 1.0 μm or more on the surface or cross section of the sintered body. The aluminum oxide phase was arranged around the crystal aggregate grains.

[0076] Comparative Example 1 A sintered body according to Comparative Example 1 was obtained in the same manner as in Example 1, except that aluminum oxide particles (second aluminum oxide) were not dry-mixed with the first raw material mixture, and only the first raw material mixture was used as a mixture. In the sintered body of Comparative Example 1, no crystal aggregate grains were observed, and the aluminum oxide phase was scattered throughout.

[0077] Comparative Example 2 A sintered body according to Comparative Example 2 was obtained in the same manner as in Example 1, except that aluminum oxide particles (second aluminum oxide particles) were not dry-mixed with the first raw material mixture, only the first raw material mixture was used as a mixture, and the temperature for firing the compact was set to 1540° C. In the sintered body of Comparative Example 2, no crystal aggregate grains were observed, and the aluminum oxide phase was scattered throughout.

[0078] Comparative Example 3 Secondary aluminum oxide particles were added so that the amount (volume %) of the secondary aluminum oxide particles was as shown in Table 1 relative to the total volume % of the first raw material mixture and the aluminum oxide particles (secondary aluminum oxide particles). 4.0 parts by mass of a dispersant (Floren G-700, Kyoeisha Chemical Co., Ltd.) was added relative to the total volume 100 parts by mass of the first raw material mixture and the secondary aluminum oxide particles, and 50 parts by mass of ethanol were further added, and the mixture was wet mixed using a ball mill, dried at 130°C for 10 hours, and then dry pulverized and mixed using a ball mill to prepare a mixture. A sintered body according to Comparative Example 3 was obtained in the same manner as in Example 1, except that the molded body obtained by molding the mixture was fired at a firing temperature of 1540°C. In the sintered body of Comparative Example 3, no crystal aggregate grains were confirmed, and the aluminum oxide phase was scattered throughout.

[0079] Comparative Example 4 A sintered body according to Comparative Example 4 was obtained in the same manner as in Comparative Example 3, except that the second aluminum oxide particles were added in an amount (volume %) shown in Table 1, relative to a total volume 100% of the first raw material mixture and the aluminum oxide particles (second aluminum oxide particles). In the sintered body of Comparative Example 4, no crystal aggregate grains were observed, and the aluminum oxide phase was scattered throughout.

[0080] The following evaluations were carried out for each sintered body. The results are shown in Table 1. In Table 1, the symbol "-" indicates that there is no corresponding item or value.

[0081] Relative Density The relative density of each sintered body of the examples and comparative examples was measured. The relative density of each sintered body of the examples and comparative examples was calculated by the above-mentioned formula (1). The apparent density of the sintered body was calculated by the above-mentioned formula (2). The true density of the sintered body was calculated by the above-mentioned formula (3). The true density of the rare earth aluminate phosphor was 6.69 g / cm. 3 , the true density of aluminum oxide particles is 3.98 g / cm 3 It is.

[0082] Transmittance (%) Using a spectrophotometer (Hitachi High-Tech Science Corporation), the light from the light source was converted to monochromatic light with a wavelength of 550 nm by a spectroscope, and the light intensity of the converted light with a wavelength of 550 nm was measured and used as the incident light intensity. The light with a wavelength of 550 nm was incident on each of the sintered bodies of the examples and comparative examples, and the light intensity of the light emitted from the sintered body on the opposite side to the incident side was measured and used as the transmitted light intensity. The ratio of the transmitted light intensity to the incident light intensity was measured as the transmittance for light with a wavelength of 550 nm based on the following formula (4). In the following formula (4), I0 is the incident light intensity, and I is the transmitted light intensity at each wavelength.

[0083]

number

[0084] Relative luminous flux (%) For each of the sintered bodies of the Examples and Comparative Examples, a laser beam having a wavelength of 450 nm was irradiated from a laser diode so that the diameter of the incident beam was 1.0 mm, and the radiant flux of the light emitted from the same surface as the surface into which the laser beam was incident was measured with an integrating sphere. The radiant flux of Comparative Example 1 was taken as 100%, and the radiant flux of each of the sintered bodies of Examples 1 and 2 and each of the sintered bodies of Comparative Examples 2 to 4 relative to the radiant flux of Comparative Example 1 was expressed as relative luminous flux (%).

[0085] Beam diameter ratio (beam diameter of outgoing light / beam diameter of incoming light) Each sintered body of the examples and comparative examples was irradiated with a laser beam having a wavelength of 450 nm from a laser diode so that the diameter of the incident beam was 0.6 mm on the first main surface where the laser beam was incident, and the diameter of the laser beam was taken as the diameter of the incident beam incident on the first main surface of the sintered body. The diameter of the outgoing beam emitted from the same surface as the first main surface where the laser beam was incident was measured by measuring the emission luminance of the light emitted from each sintered body of the examples and comparative examples with a color luminance meter, setting the position showing the maximum luminance in the obtained emission spectrum as the center (measurement center), measuring the distance (mm) from the measurement center to two positions where the luminance is 10 / 100 of the maximum luminance in the emission spectrum as an absolute value, and measuring the sum of the absolute values ​​of the distance (mm) from the measurement center to two positions where the luminance is 10 / 100 of the maximum luminance from the maximum luminance as the diameter of the outgoing beam emitted from the first main surface. The beam diameter ratio of the beam diameter of the outgoing light from the first main surface to the beam diameter of the incident light on the first main surface was calculated. The beam diameter ratio of Comparative Example 1 was set to 100%, and the beam diameter ratios of the sintered bodies of Examples 1 and 2 and Comparative Examples 2 to 4 relative to the beam diameter ratio of Comparative Example 1 were measured and expressed as relative beam diameter ratios (%).

[0086] Lighting efficiency (%) The smaller the beam diameter ratio, the smaller the area from which light is emitted (point light source), and when an optical system using a sintered body as a wavelength conversion member is used as a primary optical system and another secondary optical system is present, the light emitted from the primary optical system easily enters the secondary optical system, resulting in higher illumination efficiency. The illumination efficiency (illumination efficiency = illumination output × 100 / fluorescence output) that can be measured using a typical actual secondary optical system (e.g., a rod integrator) can be approximated by the following formula (5) using the above-mentioned relative beam diameter ratio value.

[0087]

number

[0088] Light extraction efficiency (%) For each of the sintered bodies of the Examples and Comparative Examples, the product of the measured relative luminous flux and the illumination efficiency was calculated as the light extraction efficiency. The light extraction efficiency of Comparative Example 1 was set as 100%, and the light extraction efficiency of each of the sintered bodies of Examples 1 and 2 and each of the sintered bodies of Comparative Examples 2 to 4 relative to the light extraction efficiency of Comparative Example 1 was expressed as the relative light extraction efficiency (%).

[0089] SEM images Using a scanning electron microscope (SEM), SEM images of the surface of each sintered body of the examples and comparative examples were obtained. The SEM images shown in the figures were images obtained at a magnification of 1000 times, and the SEM images used for measuring the maximum length were images obtained at a magnification of 500 times in consideration of the accuracy of the analysis. FIG. 5 is an SEM photograph of the surface of the sintered body according to Example 1. FIG. 6 is an SEM photograph of the surface of the sintered body according to Example 2. FIG. 7 is an SEM photograph of the surface of the sintered body according to Comparative Example 1. FIG. 8 is an SEM photograph of the surface of the sintered body according to Comparative Example 2. FIG. 9 is an SEM photograph of the surface of the sintered body according to Comparative Example 3. FIG. 10 is an SEM photograph of the surface of the sintered body according to Comparative Example 4.

[0090] Area ratio of aluminum oxide phase The total area of ​​the aluminum oxide phase was measured using a Winroof2018 image analysis software device (manufactured by Mitani Shoji Co., Ltd.) in the SEM images obtained by photographing the surface or cross section of each sintered body of the Examples and Comparative Examples with an SEM, and the area ratio was calculated when the measured area on the surface or cross section of the sintered body was taken as 100 area %. The measured area on the surface or cross section of the sintered body is the same as the total area 100 area % of the crystal aggregate grains and the aluminum oxide phase. In addition, since the aluminum oxide phase also exists in the thickness direction in the sintered body, the volume ratio of the aluminum oxide phase in the sintered body is approximately the same value as the area ratio of the aluminum oxide phase of the sintered body.

[0091] How to measure maximum length In the SEM images obtained by photographing the surface or cross section of each of the sintered bodies of the examples and comparative examples by SEM, 2 The area where the measurement range was determined was the area where the data size of the SEM image was 480 × 640 pixels in length × width, and one pixel was 0.396875 μm, so the area of ​​the measurement range was calculated as 190.5 μm × 254.0 μm, which is 48387 μm 2 The secondary agglomerates of one rare earth aluminate phosphor crystal phase included in this measurement range were regarded as crystal agglomerates, and the distance between the two most distant points on the contour of the crystal agglomerates was regarded as the long diameter of the crystal agglomerates, which was measured using a Winroof2018 image analysis software device (manufactured by Mitani Shoji Co., Ltd.). The distance between the two most distant points on the contour of the aluminum oxide phase (black dots on the SEM image) arranged around the crystal agglomerates was regarded as the long diameter of the aluminum oxide phase, which was measured using the image analysis software device. The long diameters of 10 to 1000 crystal agglomerates in the measurement area were measured, and the numerical value of the largest long diameter was regarded as the maximum length of the crystal agglomerates on the surface or cross section of each sintered body. In addition, the numerical value of the largest long diameter among the long diameters of the aluminum oxide phase in the aluminum oxide phase arranged around the crystal agglomerates in the measurement area was regarded as the maximum length of the aluminum oxide phase, and the presence or absence of an aluminum oxide phase with a maximum length of 1.0 μm or more was confirmed.

[0092] [Table 1]

[0093] The sintered bodies according to Examples 1 and 2 had a higher relative luminous flux than Comparative Example 1 while maintaining an excellent relative beam diameter ratio and an excellent illumination efficiency. In addition, the sintered bodies according to Examples 1 and 2 had a higher relative light extraction efficiency than Comparative Example 1. In the sintered bodies according to Examples 1 and 2, an aluminum oxide phase was arranged around the crystal aggregate grains containing the phosphor crystal phase, so that the aluminum oxide phase, which has a higher thermal conductivity than the rare earth aluminate phosphor crystal phase, absorbed the excitation light incident on the sintered body and efficiently dissipated heat when the rare earth aluminate phosphor crystal phase emitted light. The sintered bodies according to Examples 1 and 2 were able to suppress the decrease in luminous energy due to heat when the rare earth aluminate phosphor crystal phase emitted light, and were able to increase the luminous flux emitted from the sintered body. In the sintered bodies according to Examples 1 and 2, an aluminum oxide phase with a maximum length of 1.0 μm was present around the crystal aggregate grains, and the area ratio of the aluminum oxide phase in the measurement area of ​​the surface or cross section of the sintered body was within a range of 2.5 area % to 10.0 area %. From these results, the aluminum oxide phase is within the range of 2.5 vol % or more and 10.0 vol % or less relative to 100 vol % in total of the crystal agglomerates of the sintered body and the aluminum oxide phase.

[0094] The sintered bodies according to Comparative Examples 2 to 4 all had a lower relative luminous flux than the sintered body according to Comparative Example 1. The sintered body according to Comparative Example 2 had a lower firing temperature, a lower relative density than the sintered body according to Comparative Example 1, and an increased porosity. This is presumably why heat generated when the rare earth aluminate phosphor crystal phase emits light is not efficiently dissipated, resulting in a lower luminous flux than Comparative Example 1. The sintered bodies according to Comparative Examples 3 and 4 contain an aluminum oxide phase, but the aluminum oxide phase is not disposed around the crystal aggregate grains. This means that heat generated when the rare earth aluminate phosphor crystal phase emits light is not efficiently dissipated, and the decrease in luminous energy due to heat cannot be suppressed, resulting in a lower relative luminous flux than Comparative Example 1.

[0095] Fig. 5 is an SEM photograph of the surface of the sintered body according to Example 1, and Fig. 6 is an SEM photograph of the surface of the sintered body according to Example 2. It was confirmed that, in the surfaces of the sintered bodies according to Examples 1 and 2, an aluminum oxide phase 2, which appears black in the SEM photograph, is arranged around crystal aggregate grains 1 containing a rare earth aluminate phosphor crystal phase.

[0096] Fig. 7 is an SEM photograph of the surface of the sintered body according to Comparative Example 1, Fig. 8 is an SEM photograph of the surface of the sintered body according to Comparative Example 2, Fig. 9 is an SEM photograph of the surface of the sintered body according to Comparative Example 3, and Fig. 10 is an SEM photograph of the surface of the sintered body according to Comparative Example 4. In any of the SEM photographs of Fig. 7 to Fig. 10, crystal agglomerates were not observed, and it was not observed that an aluminum oxide phase was disposed around the crystal agglomerates. In the sintered bodies according to Comparative Examples 1 to 4, aluminum oxide phases 2 were scattered on the surface of the sintered bodies together with rare earth aluminate phosphor crystals 3.

[0097] The sintered body according to the present disclosure can be used in combination with an excitation light source as a wavelength conversion member for vehicle-mounted or general lighting devices, backlights for liquid crystal display devices, and light sources for projectors. [Explanation of symbols]

[0098] 1: crystal agglomerate grains, 2: aluminum oxide phase, 3: rare earth aluminate phosphor crystal phase, 100: light emitting device, 101: excitation light source, 102: collimating lens, 103, 105 and 106: condenser lenses, 104: dichroic mirror, 107: rod integrator, 110: wavelength conversion member, 111: sintered body, 112: light-transmitting thin film, 120: wavelength conversion device, 121: rotation mechanism, 122: light reflector.

Claims

1. The phosphor has a rare earth aluminate phosphor crystal phase and an aluminum oxide phase. The aluminum oxide phase is disposed around the crystal aggregate grains, A sintered body, wherein the maximum length of the crystal aggregate grains on the surface or cross section of the sintered body is within the range of 60.0 μm or more and 150.0 μm or less.

2. The sintered body according to claim 1 , comprising, in one cross-sectional view, two or more of the crystal agglomerate grains, and the aluminum oxide phase is disposed between the two or more crystal agglomerate grains.

3. 3. The sintered body according to claim 1, wherein the surface or cross section of the sintered body contains the aluminum oxide phase having a maximum length of 1.0 μm or more.

4. 3. The sintered body according to claim 1, wherein the aluminum oxide phase is contained in a surface or cross section of the sintered body in an amount of 2.5 area % or more and 10.0 area % or less relative to 100 area % of the surface or cross section.

5. 3. The sintered body according to claim 1, wherein the maximum length of the aluminum oxide phase on the surface or cross section of the sintered body is within a range of 3.0 μm or less.

6. 3. The sintered body according to claim 1, wherein the aluminum oxide phase is present in an amount of 2.5 vol% or more and 10.0 vol% or less relative to 100 vol% of the total of the crystal agglomerates and the aluminum oxide phase.

7. 3. The sintered body according to claim 1, wherein the rare earth aluminate phosphor crystal phase contains at least one element selected from the group consisting of Y, La, Lu, Gd and Tb.

8. 3. The sintered body according to claim 1, wherein the rare earth aluminate phosphor crystal phase has a composition represented by the following formula (I): (R) 1 1-n Yes n ) 3 (Al) 1-m M 1 m ) 5k O 12 (I) (In the above formula (I), R 1 is at least one element selected from the group consisting of Y, La, Lu, Gd and Tb, M 1 is at least one element selected from the group consisting of Ga and Sc, and m, n, and k satisfy 0≦m≦0.02, 0.001≦n≦0.017, and 0.95≦k≦1.10, respectively.

9. A first raw material mixture is prepared by wet mixing and then drying the first raw material mixture, the first raw material mixture comprising first oxide particles containing at least one element R 1 selected from the group consisting of Y, La, Lu, Gd and Tb, second oxide particles containing Ce, third oxide particles containing Al, and optionally fourth oxide particles containing at least one element M 1 selected from the group consisting of Ga and Sc, and optionally rare earth aluminate phosphor particles; dry-mixing the first raw material mixture with aluminum oxide particles having a BET specific surface area in the range of 1.0 m 2 / g or more and 10.0 m 2 / g or less; shaping a mixture obtained by dry-mixing the first raw material mixture and the aluminum oxide particles; and calcining the molded body obtained by molding the mixture. a sintered body obtained by firing the molded body includes crystal aggregate grains containing rare earth aluminate phosphor crystals and an aluminum oxide phase; The method for producing a sintered body, wherein the maximum length of the crystal agglomerate grains on the surface or cross section of the sintered body is within a range of 60.0 μm or more and 150.0 μm or less.

10. The method for producing a sintered body according to claim 9 , wherein a BET specific surface area of ​​the aluminum oxide particles is smaller than a BET specific surface area of ​​the third oxide particles containing Al.

11. The BET specific surface area of ​​the third oxide particles containing Al is 10.0 m 2 / g exceeds 15.0 m 2 The method for producing a sintered body according to claim 9 or 10, wherein the surface roughness is in the range of 0.1 μm to 1.0 μm.

12. 11. The method for producing a sintered body according to claim 9 or 10, wherein the aluminum oxide particles are contained in a range of 2.5 vol% to 10.0 vol% relative to 100 vol% of a total amount of the first raw material mixture and the aluminum oxide particles.

13. The method for producing a sintered body according to claim 9 or 10, wherein the sintering temperature when sintering the molded body is within a range of 1300° C. or more and 1800° C. or less.

Citation Information

Patent Citations

  • Ceramic composite

    JP2013227481A

  • Fluorescent member, manufacturing method therefor and light emitting device

    JP2016204561A

  • Strongly scattering ceramic converter and method for producing the same

    JP2017197774A

  • Ceramic composite, and fluophor for projector and light emitting device containing the same

    JP2019006967A

  • Fluorescent body, wavelength conversion element, light source device, and projector

    JP2020132847A